Penerapan Model Pembelajaran Problem Based Learning terhadap Hasil Belajar IPA Kelas IX SMP Negeri 5 Kotawaringin Lama - Beny Saputra; Alimin Alimin; Asri Asri (Celebes Science Education, 2022)
This study aims to increase the learning outcomes of class IX science at SMP Negeri 5 Kotawaringin lama. This study uses a Problem Based Learning model. Data collection techniques were carried out with tests and non-tests, with data collection tools in the form of student activity observation sheets, teacher activity observation sheets, and final test sheets for each cycle. The procedures for implementing this research include: (1) planning, (2) implementing actions, (3) observing, and (4) reflecting in each cycle. The Student Activity Observation Sheet technique showed that there was an increase in student learning outcomes from cycle I to cycle II and from cycle II to cycle III. The percentage of learning completeness in Cycle I was 68,75 %, Cycle II was 75.00 % and Cycle III was 93.75 %. The average learning outcomes in the first cycle is 72.43, the second cycle is 74.75 and the third cycle is 78.31. The results of the research above prove that the Problem Based Learning learning model can increase the learning outcomes of science class IX SMP Negeri 5 Kotawaringin lama.